(untitled) (Journal of Plant Disease Sciences, 2025)
Green gram ( L.) is one of the most important legume crops which is a rich source of protein (24.5%), fat (1.3%), minerals (3.5%) and Carbohydrates (56.7%). Anthracnose disease of green gram caused by Colletotrichum lindemuthianum is a major fungal disease causing serious loss of 24 to 67% both qualitative and quantitatively. The current study aimed to test the efficacy of bioagents and fungicides against anthracnose of green gram. Five fungal bioagent and two bacterial bioagent were evaluated against Colletotrichum lindemuthianum under condition. All the biocontrol agents were showed wide range of inhibitory patterns. and was proved to be most effective inhibiting the pathogen as 100% inhisition recorded against the test pathogen. Total seven fungicides were tested at two different concentrations (1500 and 2000 ppm) against the pathogen by using poisoned food technique. Amongst the tested fungicides, Azoxystrobin + mancozeb showed highest inhibition (100%) at both concentrations.